2008
DOI: 10.21307/ijssis-2017-307
|View full text |Cite
|
Sign up to set email alerts
|

Guidance-Based On-Line Motion Planning For Autonomous Highway Overtaking

Abstract: In the context of intelligent transportation, this paper presents a novel on-line trajectorygeneration method for autonomous lane changing. The proposed scheme is guidance based, realtime applicable, and ensures safety and passenger ride comfort. Based on the principles of Rendezvous Guidance, the passing vehicle is guided in real-time to match the position and velocity of a shadow target (i.e., rendezvous with) during the overtaking manoeuvre. The shadow target's position and velocity are generated based on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Inter-disciplinary techniques inspired by robotics and missile guidance systems [5,55,56] for vehicle path-planning are also reported in literature. One of the novel approaches proposed was to use motion primitives (combination of steady-state equilibrium trajectories and pre-specified manoeuvres) [57].…”
Section: Cell Decomposition Algorithms Such As Rapidly-exploring Randmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-disciplinary techniques inspired by robotics and missile guidance systems [5,55,56] for vehicle path-planning are also reported in literature. One of the novel approaches proposed was to use motion primitives (combination of steady-state equilibrium trajectories and pre-specified manoeuvres) [57].…”
Section: Cell Decomposition Algorithms Such As Rapidly-exploring Randmentioning
confidence: 99%
“…The experimental results demonstrated that collision free and feasible trajectories can be generated in real-time using this approach [57]. Ghumman et al designed a trajectory planning method based on Rendezvous Guidance technique (passing vehicle is guided in real-time to match the position and velocity of a shadow target during an overtaking manoeuvre) inspired from missile guidance systems [55,56], see Figure 5c. Similarly, an approach for overtaking manoeu-vre consisting of consecutive tracking of virtual reference points positioned a priori at known distances from the lead vehicle is proposed in [5].…”
Section: Cell Decomposition Algorithms Such As Rapidly-exploring Randmentioning
confidence: 99%
“…The solution of the optimization problem determines the optimal time and distance for the lane change maneuver using 5-th degree polynomial functions. An on-line time-optimal trajectory planning algorithm for the guidance of a pursuer vehicle overtaking a slower vehicle which is based on Rendezvous-Guidance principle was proposed in [36]. Two-layer controller architecture for overtaking maneuver is presented in [37].…”
Section: Modeling and Nonlinear Adaptive Control For Autonomous Vehicmentioning
confidence: 99%
“…The change in behavior coupled with the lack of the awareness of the global scenario of the traffic state for spatial temporal anticipation and reduced maneuvering time may result in collision when the front or side ahead vehicle brakes or during lane changing on the highways. Absolute errors in the decision-making time typically caused by driver at the time of lane change failure to accurately and timely interpret information about other vehicles in close proximity, have often resulted in serious accidents and congestion on the highways [32], [33].…”
Section: Driver Behavior During Lane Change Processmentioning
confidence: 99%